Perpustakaan Digital Sebagai Sarana Media Promosi Bagi Masyarakat - Sari, Dinar Mustika; Sudarsana, Undang (Media Nusantara, 2022)
The purpose of this research is to analyze the digital library as a promotional medium for the community, by describing the development of information in the library is growing rapidly and because of that the public’s need for a library should be growing. This article wascompiled using a literature study approach. Literature studies obtain sources from journals,books, internet, and libraries. Literature studies get sources from journals, books, internet,and literature. In this research, the author will collect sources relevant to the research topic,sources that support this research based on several journals and other reference sources.Information technology has become a necessity for libraries in Indonesia, especially to dealwith the demands of the knowledge-based needs of the Indonesian people for information inthe future. Some of the things that underlie the idea of the need to digitize libraries are thedevelopment of information technology in computers increasingly opening new opportunities for the development of library information technology that is cheap and easy to implementby Indonesian libraries. The role of digital libraries can be transformed not only as aninformation center but also as a forum for development in society to improve welfare.